Persistent impairment on spirometry in chronic eosinophilic pneumonia: A longitudinal observation study (Shizuoka-CEP study). - Suzuki, Yuzo; Oyama, Yoshiyuki; Hozumi, Hironao; Imokawa, Shiro; Toyoshima, Mikio; Yokomura, Koshi; Nakamura, Hidenori; Kuroishi, Shigeki; Karayama, Masato; Furuhashi, Kazuki; Enomoto, Noriyuki; Fujisawa, Tomoyuki; et al. (Annals of Allergy, Asthma & Immunology, 2017)
Background: Chronic eosinophilic pneumonia (CEP) is characterized by the accumulation of eosinophils in the lung with unknown etiology. Although systemic corticosteroid administration leads to dramatic improvement, nearly half the patients with CEP experience relapse and some develop persistent impairment of pulmonary function. However, predictive factors for this persistent impairment have not been determined.Objective: To investigate the occurrence of persistent impairment of pulmonary function in CEP and determine its predictive factors.Methods: This observational study consisted of 133 consecutive patients with CEP who were followed for longer than 1 year. Spirometry was performed at the time of diagnosis and at follow-up.Results: During the observational period (6.1 ± 4.1 years), relapse occurred in 75 patients (56.4%). Remarkably, 42 patients (31.6%) had a persistent pulmonary function defect (27 obstructive, 10 restrictive, and 4 obstructive and restrictive cases) at the last evaluation. Logistic analyses showed that the relapse was associated with neither persistent obstructive nor restrictive defects. Persistent obstructive defect was significantly associated with the comorbidity of asthma and obstructive defect at the initial CEP diagnosis, whereas persistent restrictive defect was significantly related to reticulation at high-resolution computer tomography and restrictive defect at diagnosis.Conclusion: Persistent impairment of pulmonary function is common in CEP. Concurrent asthma and obstructive defects at diagnosis were predictors for persistent obstructive impairments, whereas reticulation at high-resolution computer tomography and restrictive defect at diagnosis predicted persistent restrictive impairment. Attention should be paid to these persistent impairments in the management of CEP.Trial Registration: http://www.umin.ac.jp/ctr/index-j.htm Identifier: UMIN000019092 (principal investigator, Takafumi Suda, MD, PhD).